Administrative responses to the identity problems and social tensions of the tribal communities in North-East India - Bhadra, R.K. (2002)
Preservation of tribal identity and culture is seen here as the main demand from north-eastern states of India. Decline of political status of the tribal chiefs and assimilation of communities with non-trible people from adjoining plains has been perceived as a threat to their identity and existence. An analyses has been made in this article as to how insurgent movements by various tribes and regions were directed at achieving freedom from the `alien' rulers and establishing their own rule under traditional system of self-governance. A promise of restoring their political economy and preserving their identity tyhrough their culture, language and social values garnered mass support for these movements. The author evaluates efficacy of successive administrative and political initiatives to bring peace to the region. - Reproduced.
Keywords: Social conflicts; Politics and government